ANALISIS CAMPURAN ASPAL AC-WC PG 76 DENGAN ADDITIONAL FILLER ABU BAMBU TERHADAP FLEKSIBILITAS DAN DURABILITAS - Abdi Rachman Sidiq; Farlin Rosyad; Ely Mulyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Highways are an essential land transportation infrastructure, and the quality of pavement must be maintained to ensure performance and service life. One effort to improve the quality of flexible pavement on the Asphalt Concrete-Wearing Course (AC-WC) layer is by utilizing alternative materials as filler. This study examines the effect of adding bamboo ash as an additional filler in AC-WC mixtures with PG 76 asphalt on flexibility (flow) and durability (Marshall Retained Stability). Bamboo ash contains silica (SiO₂) and exhibits pozzolanic properties, which have the potential to enhance mixture performance. The bamboo ash content variations used were 0%, 0.5%, 1.0%, 1.5%, and 2.0% by the total aggregate weight, with testing conducted using the Marshall Test method. The results showed that the addition of 0.5% bamboo ash increased the flow value from 3.32 mm to 3.52 mm, while further additions above this level did not result in additional flexibility improvement. All mixture variations had Marshall Retained Stability values above the minimum requirement of PU Bina Marga 2018 Revision 2 (≥90%), with the highest value recorded at 0.5% (91.47%). Based on the balance between flexibility and durability, the optimal bamboo ash filler content for AC-WC PG 76 is 0.5%.Keywords : AC-WC, bamboo ash, PG 76 asphalt, flexibility, durability, Marshall Test.